Long-term alterations on the physical development of pre- and neonatally undernourished Wistar rats: a functional correlation - Ortiz-Valladares, Minerva; Salcedo, Claudia A; Regalado Ortega, Mirelta; Torrero Solorio, Carmen; Salas Alvarado, Manuel (Revista eNeurobiología, 2019)
La restricción temprana de alimento en la rata interfiere en el largo plazo con el desarrollo físico y la función cerebral, aunque los parámetros del sistema esquelético asociados a la desnutrición pre y neonatal han sido poco estudiados. Se Compararon los efectos de la desnutrición gestacional y por la ligadura materna (UL), con los de la desnutrición en una incubadora (UI) asociada a privación sensorial en el desarrollo físico de ratas Wistar hembras y machos F1 y machos adultos F1. Las madres UL F0 recibieron restricción calórica prenatal de alimento. En la lactancia, una de un par de madres se ligó de sus conductos galactóforos intercambiándose entre las camadas (12 h) con otra sin ligadura. Los sujetos con UI permanecieron en una incubadora durante 12 h. Entre los días postnatales (PDs) 5-90 se midieron los ejes longitud del cráneo, bitemporal, naso-cóccix, cola, tarso-metatarso y longitud de falanges, peso corporal, tamaño corporal medio y apertura palpebral. Los sujetos UL y UI mostraron déficits esqueléticos significativos después de una dieta normocalórica desde el PD 25 hasta el 90 vs. sus controles. Además, mostraron pesos corporales significativamente bajos tanto en los sujetos UL hembras o machos, como en los sujetos con UI al compararse ambos grupos. El índice de masa corporal (BMI) en el día PD 90 en hembras con UI mostró un porcentaje mayor vs. sus controles. Se sugiere que la desnutrición perinatal alteró el desarrollo físico de los sujetos F1, afectando su actividad sensoriomotora y las respuestas adaptativas sociales tardías. Abstract: Early food restriction resulted in long-term consequences on physical and brain development. However, long-term skeletal maturity parameters interacting with sensory deprivation are scarcely described. We compare the effects of gestational undernutrition and postnatal ligature (UL) and neonatal undernutrition by using an incubator (UI) with sensory deprivation on the physical development of suckling and adult F1 female and male Wistar rats. UL F0 subjects were submitted to caloric food restriction during the gestational period and suckling of dams, one with nipple-ligated and interchanged every 12 h. UI subjects were underfed by placing pups into one incubator for 12 h. Skull, nose-coccyx, tail, tarsus-metatarsus, phalange lengths, bitemporal axis, body weight, mean body sizes and eyelid opening were measured on postnatal days (PDs) 5-90. UL and UI subjects resulted with significant skeletal deficits following a normocaloric diet from PD 25 in most of the ages from PDs 5 to 90 of the study compared with their controls. Furthermore, significant low body weights in both female and male UL groups throughout the lactation period, compared to normally feeding rats were obtained. Body Mass Index (BMI) on PD 90 in female UI subjects showed higher percentages than controls. The findings indicated that gestational undernutrition of F0 dams resulted in consistent, long-term altered physical development of F1 subjects that might interfere with their body growth, sensorimotor activity and possibly with the late social adaptive responses. Keywords: Early undernutrition; physical development; rats; sensory manipulation; growth.